Prevalence and Antimicrobial Resistance of Enterococcus Species: A Hospital-Based Study in China - Jia, Wei (MDPI, 2014)
Objective: to investigate the prevalence and antimicrobial resistance of Enterococcus species isolated from a university hospital, and explore the mechanisms underlying the antimicrobial resistance, so as to provide clinical evidence for the inappropriate clinical use of antimicrobial agents and the control and prevention of enterococcal infections. Methods: a total of 1,157 enterococcal strains isolated from various clinical specimens from January 2010 to December 2012 in the General Hospital of Ningxia Medical University were identified to species level with a VITEK-2 COMPACT fully automated microbiological system, and the antimicrobial susceptibility of Enterococcus species was determined using the Kirby-Bauer disc diffusion method. The multiple-drug resistant enterococcal isolates were screened from the clinical isolates of Enterococcus species from the burns department. The minimal inhibitory concentration (MIC) of Enterococcus species to the three fluoroquinolones, including ciprofloxacin, gatifloxacin and levofloxacin was determined with the agar dilution method, and the changes in the MIC of Enterococcus species to the three fluoroquinolones following reserpine treatment were evaluated. The β-lactam, aminoglycoside, tetracycline, macrolide, glycopeptide resistance genes and the efflux pump emeA genes were detected in the enterococcal isolates using a polymerase chain reaction (PCR) assay. Results: the 1,157 clinical isolates of Enterococcus species included 679 E. faecium isolates (58.7%), 382 E. faecalis isolates (33%), 26 E. casseliflavus isolates (2.2%), 24 E. avium isolates (2.1%), and 46 isolates of other Enterococcus species (4%). The prevalence of antimicrobial resistance varied significantly between E. faecium and E. faecalis, and ≤1.1% of these two Enterococcus species were found to be resistant to vancomycin, teicoplanin or linezolid. In addition, the Enterococcus species isolated from different departments of the hospital exhibited various resistances to the same antimicrobial agent, while reserpine treatment reduced the resistance of Enterococcus species to ciprofloxacin, gatifloxacin and levofloxacin. The β-lactamase gene TEM, aminoglycoside-modifying-enzyme genes aac(6')-aph(2"), aph(3')-III, ant(6)-I and ant(2")-I, tetracycline resistance gene tetM, erythromycin resistance gene ermB, vancomycin resistance gene vanA and the enterococcal multidrug resistance efflux emeA gene were detected in 77%, 62%, 26%, 13%, 36%, 31%, 66%, 5% and 55% of the 100 multiple-drug resistant enterococcal isolates. Conclusions: similar to previous findings, E. faecium and E. faecalis are predominant conditionally pathogenic bacteria that cause hospital-acquired infections that can cause urinary and respiratory system infections. Multiple and high-level antimicrobial resistance is highly prevalent in the hospital isolates of Enterococcus species. Reserpine treatment inhibits the active efflux of Enterococcus species to ciprofloxacin, gatifloxacin and levofloxacin in vitro and reduces the MIC of Enterococcus species to these three fluoroquinolones. The presence of the enterococcal multidrug resistance efflux emeA gene is associated with the resistance to antibiotics in Enterococcus species. The monitoring of the prevalence and antimicrobial resistance of Enterococcus species is of great significance to guide the control and prevention of enterococcal infections.